Sobrecarga y ansiedad en cuidadores primarios de usuarios del Centro Diurno de Desarrollo Integral para Personas con Discapacidad Loja, 2021- 2022 - Apolo Carrión, Karen Anahí (2022)
The overload of the caregiver of a person with disabilities is a public health issue because the continuous care of his or her family member entails a series of complications at the physical and psychological level, generating a decline in their daily activities and causing loss of their independence and self-care. Thus, the general objective of this study was to determine the influence of overload levels on the anxiety of primary caregivers at the Comprehensive Development Day Centre for Persons with Disabilities in the city of Loja. The specific objectives include to identify the overload level, to describe the prevailing anxiety level and to design an intervention plan. The study had a quantitative approach of nonexperimental design with a cross-sectional, descriptive and correlative section. The sample consisted of 45 primary caregivers to whom a sociodemographic record, the Zarit Caregiver Overload Scale and the Beck Anxiety Inventory were applied. The results indicate that there is a statistically significant correlation between overload and anxiety, showing that, the higher the level of overload, the primary caregiver generates a higher level of anxiety. In addition, 55.60% of the population are heavily overburdened, 11.10% maintain a low level of overload and the remaining 33.30% have a slight overload. Regarding anxiety, 40% of the population shows a high level of anxiety, followed by moderate anxiety with 22.2%, mild anxiety with 13.30% and the remaining 24.40% with minimal anxiety